Gender Empowerment as a Strategy for National Development In Nigeria - Asaju, Kayode; Matakhitswen, Kefas (ILIN Education Indonesia, 2024)
Gender empowerment is currently the main focus of attention from researchers, governments, and other stakeholders. The concept of women's empowerment contains various meanings. This paper attempts to look into gender empowerment as a strategy for national development with more focus on women. The data for this study is generated through secondary sources of data collection from journals, textbooks, and materials from the internet. The study recommends that Nigerian government policy should always consider the female gender for necessary support, and upliftment, as this will help to improve their status and enhance national development in Nigeria. Across the country, there is an urgent need for women's development and self-employment training institutes. Empowerment programs initiated by successive governments should be sustained and not allowed to waste. In other words, there should be continuity of programs after each government has left office. The issue of maintenance culture should be revisited and imbibed by government agencies and all stakeholders in development so that the various empowerment programs will not be abandoned and resources invested in the programs wasted.